Elevated Serum IgG4 Levels in Diagnosis, Treatment Response, Organ Involvement, and Relapse in a Prospective IgG4‐Related Disease UK Cohort. (May 2016) - Culver, Emma L; Sadler, Ross; Simpson, Dawn; Cargill, Tamsin; Makuch, Mateusz; Bateman, Adrian C; Ellis, Anthony J; Collier, Jane; Chapman, Roger W; Klenerman, P; Barnes, Eleanor; Ferry, Berne
Abstract : OBJECTIVES: Elevated serum immunoglobulin G4 (IgG4) levels have been associated with autoimmune pancreatitis and IgG4‐related disease (IgG4‐RD) for over a decade. However, an elevated serum IgG4 is not specific for the disease. There have been inconsistent reports of its use in diagnosis, as a marker of disease relapse, and its relationship to organ involvement in retrospective cohorts. The aims of this study were to ascertain conditions that are associated with an elevated serum IgG4 and to investigate the role of IgG4 in diagnosis, relapse, and organ involvement in a prospective cohort of patients with IgG4‐RD. METHODS: We evaluated serum IgG4 measurements in the Oxford Immunology Laboratory over 6 years. Patients in whom serum IgG4 was requested to differentiate IgG4‐RD from other diseases were recruited into a longitudinal follow‐up study to determine final diagnosis. In a prospective cohort of IgG4‐RD patients, organ involvement, response to therapy, and disease relapse were determined. RESULTS: Two thousand and sixty‐seven samples from 1, 510 patients had serum IgG4 measured. Of these, IgG4 was elevated (≥1.4 g l −1 ) in 243 (16.1%) patients. The main indication (85.6%) was to distinguish between IgG4‐RD and non‐IgG4‐RD conditions. Only 5.1% of patients who had serum IgG4 measured for this purpose had a final diagnosis of IgG4‐RD. Of those with an elevated serum IgG4, 22.4% met IgG4‐RD diagnostic criteria. Serum IgG4 was elevated in 48 (82.8%) of IgG4‐RD patients. An IgG4 cutoff of 1.4 g l −1 gave a sensitivity of 82.8% and specificity of 84.7% to diagnose IgG4‐RD. Increasing this to 2.8 g l −1 increased specificity to 96.2% and negative predictive value to 97.7%, with a lower sensitivity of 56.9% and positive predictive value of 44.5%. Serum IgG4 levels fell with corticosteroid therapy, but this was not disease‐specific. A serum IgG4 of ≥2.8 g l −1 at diagnosis was associated with multi‐organ involvement and risk of relapse. CONCLUSIONS: Serum IgG4 levels are elevated in multiple non‐IgG4‐RD inflammatory and malignant conditions, with less than one‐quarter of those with an elevated IgG4 meeting IgG4‐RD diagnostic criteria. A serum IgG4 of ≥2.8 g l −1 is useful in distinguishing between IgG4‐RD and non‐IgG4‐RD diagnoses, predicting multiple‐organ involvement and risk of relapse in IgG4‐RD.